Effect of nitrogen arc discharge plasma treatment on physicochemical properties and biocompatibility of PLA-based scaffolds - Laput, Olesya A.; Vasenina, Irina V.; Korzhova, Alena G.; Bryuzgina, Anastasia A.; Khomutova, Ulyana V.; Tuyakova, Sitora G.; Ahmadeev, Yury Kh; Shugurov, Vladimir V.; Bolbasov, Evgeny N.; Tverdokhlebov, Sergey I.; Chernyavskii, Aleksandr V.; Kurzina, Irina A. (Polymers)
The effect of low-temperature arc discharge plasma treatment in a nitrogen atmosphere on the modification of the physicochemical properties of PLA-based scaffolds was studied. In addition, the cellular-mediated immune response when macrophages of three donors interact with the modified surfaces of PLA-based scaffolds was investigated. PLA surface carbonization, accompanied by a carbon atomic concentration increase, was revealed to occur because of plasma treatment. Nitrogen plasma significantly influenced the PLA wettability characteristics, namely, the hydrophilicity and lipophilicity were improved, as well as the surface energy being raised. The viability of cells in the presence of the plasma-modified PLA scaffolds was evaluated to be higher than that of the initial cells.